Multidimensional Value Analysis of Comprehensive Rural Revitalization in Ethnic Regions - Wang, Meihong (Journal of Social Science and Humanities, 2025)
The arduous and heavy task of modernization in ethnic regions still lies in rural areas. Comprehensively promoting the comprehensive revitalization of rural areas is the main problem that must be addressed in the later stage of modernization in ethnic regions, and it is a key measure to alleviate the contradiction of unbalanced and insufficient development in ethnic regions. Therefore, it is necessary to scientifically sort out and clarify the issues that urgently need to be addressed in the comprehensive revitalization of rural areas in ethnic regions, such as the erosion of rural space, compression of living space, bottlenecks in development foundations, and the price gap, income gap, resource gap, and basic public service gap between urban and rural agricultural and animal husbandry products. It is of great significance to more accurately stimulate the endogenous power enhancement efficiency in ethnic regions, promote the coupled development of ethnic regions, and promote the coordinated development of comprehensive rural revitalization and common prosperity goals in ethnic regions.